Short-Scar Latissimus Dorsi With a Lateral Approach: A Game Changer in Breast Reconstruction?. (24th May 2021) - Perez, Simon; Delay, Emmanuel; Sinna, Raphaël; Savu, Traian; Vaucher, Richard; Frobert, Paul
Abstract: Background: In delayed breast reconstruction, the thoraco-mammary cutaneous tissue often shows residual damage from radiotherapy. The fragility of this tissue is associated with a risk of skin necroses of approximately 8% when dissection is performed by reopening of the mastectomy scar. Objectives: The objective of this study was to adapt the technique of short-scar latissimus dorsi flap surgery with an abdominal advancement flap employing a lateral approach only avoiding re-incision of the mastectomy scar. Methods: In this retrospective study, the authors performed 150 reconstructions in 146 patients to assess the safety and effectiveness of the short-scar latissimus dorsi technique with lateral approach. The primary outcome was the occurrence of postoperative skin necrosis of the thoraco-mammary area. Results: Of the 150 delayed breast reconstruction procedures performed, none showed skin necrosis of the thoraco-mammary area, and a positive effect on skin trophicity of this area was observed. The resulting patient and surgical team satisfaction were very favorable. Conclusions: In the authors' practice, this technique changed their paradigm because of good skin safety and effectiveness. It allows reconstruction without a patch-effect in patients with very poor skin quality in whom the thoraco-mammary skin would have been replaced in the past by a skin paddle. Reconstruction would have even be contraindicated. It could also be an alternative to many other more complex and longer techniques of autologous reconstruction. Level of Evidence: 4: